Accommodating Students With Special Educational Needs During School Closures Due to the COVID-19 Pandemic in Norway: Perceptions of Teachers and Students - Cameron, David Lansing; Matre, Marianne Engen; Canrinus, Esther Tamara (Frontiers in Education, 2022)
The purpose of the two interrelated studies reported here was to explore the approaches that schools and teachers adopted to accommodate students with special educational needs (SEN) during school closings in Norway, as well as the consequences of the pandemic for children with SEN and their peers. Study 1 was a mixed-methods case study of a lower-secondary school in which students with SEN (n =14) and students performing at or above grade-level (n = 66) completed a survey about their experiences. Survey results were then used as a starting point for follow-up interviews with four teachers and the school principal to explore how they dealt with pandemic restrictions and supported students with SEN. Study 2 is based on a survey of teachers from 10 schools (n = 128) who were participating in a professional development course on the use of educational technology when pandemic restrictions were enacted. Findings from both studies indicate that teachers and pupils are most concerned about the social and emotional consequences of the pandemic and report that distance learning worked poorly for pupils with SEN. For this reason, many students with SEN were provided with teaching at school while their classmates remained at home. Overall, teachers and students believe that they coped well given the circumstances and that the long-term impact on most students will be minimal. However, findings from both studies point to areas of concern for students with SEN and other pupils who were already struggling prior to the shutdown, citing a failure to meet the needs of these students through digital home-schooling and a loss of the support that students have a legal right to receive.